Write the following expression using the fewest possible terms:
( 5 + 38
y) + (14
y - 2)
(1 point)
Responses
1/8 y − 3
1/8 y − 3
1/8 y + 3
1/8 y + 3
5/8 y − 3
5/8 y − 3
5/8 y + 3
5/8 y + 3
11 answers
The correct expression using the fewest possible terms is: 5/8y + 3.
Simplify the expression. (7x+6) - (8+x)
To simplify the expression (7x + 6) - (8 + x), you can distribute the negative sign to both terms inside the second parentheses:
7x + 6 - 8 - x
Next, combine like terms:
(7x - x) + (6 - 8)
This simplifies to:
6x - 2
Therefore, the simplified expression is 6x - 2.
7x + 6 - 8 - x
Next, combine like terms:
(7x - x) + (6 - 8)
This simplifies to:
6x - 2
Therefore, the simplified expression is 6x - 2.
Select ALL equivalent expressions to: (7x-2) - (0.04x-3+0.2x)
To simplify (7x - 2) - (0.04x - 3 + 0.2x), let's distribute the negative sign inside the second parentheses:
(7x - 2) - 0.04x + 3 - 0.2x
Combine like terms:
7x - 2 - 0.04x + 3 - 0.2x
Simplify further:
(7x - 0.04x - 0.2x) + (-2 + 3)
Combine like terms:
(6.76x) + (1)
Since there are no like terms to combine further, the simplified expression is:
6.76x + 1
Therefore, the equivalent expression is 6.76x + 1.
The other expressions listed are NOT equivalent to the given expression.
So the correct answer is:
6.76x + 1
(7x - 2) - 0.04x + 3 - 0.2x
Combine like terms:
7x - 2 - 0.04x + 3 - 0.2x
Simplify further:
(7x - 0.04x - 0.2x) + (-2 + 3)
Combine like terms:
(6.76x) + (1)
Since there are no like terms to combine further, the simplified expression is:
6.76x + 1
Therefore, the equivalent expression is 6.76x + 1.
The other expressions listed are NOT equivalent to the given expression.
So the correct answer is:
6.76x + 1
Jill is thinking of a number. Four more than three times the number is thirteen. What is the number?
Jill's number is ____
Jill's number is ____
Let's represent Jill's number as "x". The problem states that "Four more than three times the number is thirteen", which means:
3x + 4 = 13
To solve for x, we can subtract 4 from both sides:
3x = 13 - 4
3x = 9
Finally, we can divide both sides by 3 to find the value of x:
x = 9/3
Simplifying, we get:
x = 3
Therefore, Jill's number is 3.
3x + 4 = 13
To solve for x, we can subtract 4 from both sides:
3x = 13 - 4
3x = 9
Finally, we can divide both sides by 3 to find the value of x:
x = 9/3
Simplifying, we get:
x = 3
Therefore, Jill's number is 3.
What is the value of y in the equation below?
6(y-1.5)=30
6(y-1.5)=30
To find the value of y in the equation 6(y - 1.5) = 30, we need to solve for y.
We can start by distributing the 6 to both terms inside the parentheses:
6y - 9 = 30
Next, we can isolate the y term by adding 9 to both sides of the equation:
6y = 30 + 9
6y = 39
Finally, we divide both sides of the equation by 6 to solve for y:
y = 39/6
Simplifying the fraction, we get:
y = 6.5
Therefore, the value of y in the equation is 6.5.
We can start by distributing the 6 to both terms inside the parentheses:
6y - 9 = 30
Next, we can isolate the y term by adding 9 to both sides of the equation:
6y = 30 + 9
6y = 39
Finally, we divide both sides of the equation by 6 to solve for y:
y = 39/6
Simplifying the fraction, we get:
y = 6.5
Therefore, the value of y in the equation is 6.5.
To rent a car you need to pay a flat fee plus $0.20 for each mile that you drive. Which equation could be used to solve for the price of the initial fee if the total cost of a rental was $60 when the car was driven 40 miles?
Let's represent the initial fee as "x" and the number of miles driven as "m".
The total cost of a rental includes the flat fee plus $0.20 for each mile driven.
So, the equation to solve for the price of the initial fee is:
x + 0.20m = Total cost
In this case, the total cost is given as $60 and the number of miles driven is given as 40. Plugging in these values to the equation, we get:
x + 0.20(40) = 60
Now we can solve for x:
x + 8 = 60
Subtracting 8 from both sides:
x = 60 - 8
x = 52
Therefore, the equation to solve for the price of the initial fee is x + 0.20m = 60, where x = 52.
The total cost of a rental includes the flat fee plus $0.20 for each mile driven.
So, the equation to solve for the price of the initial fee is:
x + 0.20m = Total cost
In this case, the total cost is given as $60 and the number of miles driven is given as 40. Plugging in these values to the equation, we get:
x + 0.20(40) = 60
Now we can solve for x:
x + 8 = 60
Subtracting 8 from both sides:
x = 60 - 8
x = 52
Therefore, the equation to solve for the price of the initial fee is x + 0.20m = 60, where x = 52.